2013
DOI: 10.13005/bbra/1167
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Transformation of Bioactive Anthraquinones ? A Review

Abstract: Anthraquinones, especially hydroxyanthraquinones, constitute one of the most ubiquitous classes of naturally occurring phenolic compounds. The hydroxyl and aminoanthraquiones show diverse physiological and pharmacological activity. Since pharmacological studies of small molecule bioactive compounds are known to be hampered by their weak solubility in water, it is important to prepare water-soluble analogues of hydroxyand aminoanthraquinones by biotransformation. This review summarizes the glucosidation of subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…The presence of alkaloids, anthraquinones, flavonoids, phenolics and saponins in the aqueous acetic acid fruit extracts may justify the cytotoxic activity of A. racemosa. [22,24,28,29] Furthermore, present results support previous studies on the medicinal value of A. racemosa fruit. As have been reported, A. racemosa fruit exhibited anti-inflammatory, [18] antibacterial, [20,21] antifungal and analgesic properties.…”
Section: Brine Shrimp Lethalitysupporting
confidence: 89%
See 1 more Smart Citation
“…The presence of alkaloids, anthraquinones, flavonoids, phenolics and saponins in the aqueous acetic acid fruit extracts may justify the cytotoxic activity of A. racemosa. [22,24,28,29] Furthermore, present results support previous studies on the medicinal value of A. racemosa fruit. As have been reported, A. racemosa fruit exhibited anti-inflammatory, [18] antibacterial, [20,21] antifungal and analgesic properties.…”
Section: Brine Shrimp Lethalitysupporting
confidence: 89%
“…Moreover, a number of researches have shown that phenolics, flavonoids, saponins, alkaloids and anthraquinones have cardioprotective, anti-inflammatory, antioxidative, free radical scavenging, antimicrobial, anticancer and analgesic activities. [17,[22][23][24]…”
Section: Brine Shrimp Lethalitymentioning
confidence: 99%
“…The activity of several hydroxyl- and amino-anthraquinones cannot be exploited due to their weak solubility in water. Thus, some of them are converted into water-soluble analogues by biotransformation [ 8 ]. Anthraquinones have also industrial application as natural dyes substituting synthetic chemicals in formulation to avoid undesired collateral effects [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports on microbial conversion of steroids have been published during the last half-century [9,6,[10][11][12][13][14][15][16][17][18][19][20][21] focusing mainly on steroidal dehydrogenation, hydroxylations, esterification, halogenations, isomerization, methoxylation, and side-chain cleavage [22,23]. In continuation of our work on microbiotransformation [24][25][26][27][28] for the first time, we report here the fermentation of finasteride (1) with Macrophomina phaseolina (ATCC730) in order to obtain further microbial derivatives of finasteride which can be future candidates of drugs. Chemicals and reagents spraying reagent was used for the staining of compounds on TLC.…”
Section: Introductionmentioning
confidence: 99%